Predictive Optimal Iterative Learning Control for Nonlinear Systems using the Koopman Operator - Tao, Xinyue; Tao, Hongfeng; Gao, Luyuan; Paszke, Wojciech (1975- ); Rogers, Eric
This paper develops a predictive optimal iterative learning control design for nonlinear systems based on the Koopman operator. Iterativa learning control applies to systems that make repeated executions, known as trials, over a finite duration, termed the trial length. Once a trial is complete, all information generated is available to update the control signal for the subsequent trial.
Keywords: iterative learning control; nonlinear systems; Koopman operator; predictive action